Citologia dos liquidos extra-embrionários e morfometria do placentomo da vaca nos terços inicial, médio e final da gestação - Maria Raquel Pereira Moura (2008)
The aim of this study was to quantificate maternal cells and evaluate the volumetric proportions of structural components of crossbreed Holstein/Zebu cow placentome in the first, second and third trimester of pregnancy. For each trimester were used ten pregnant uteri, collected in slaughterhouse. The trimester of pregnancy was determinated using the crown-rump length. The placentomes were fixed in formol 10% and processed for histological examination. At the third trimester the maternal cells of the placentome decreased. The volumetric proportions of the fetal cells, binucleate cells, giant cells and vessels did not vary during gestation, while the one of the maternal cells decreased on the third trimester of pregnancy, and the one of the fetal placentome conjunctive tissue was lower in the first trimester. The maternal conjunctive tissue was higher in the third trimester of pregnancy. The results show that the number of maternal cells and the volumetric proportion of some structural components of the crossbreed Holstein/Zebu cow placentome change during pregnancy